The Effects of Allograft Combined with Ozone Therapy on Regeneration of Calvarial Defects in Rats - Hülya Toker (Cumhuriyet University, 2017)
Objective: Ozone accelerates wound healing and increases oxygen supply. The purpose of this study was to investigate the effect of ozone therapy combined with bone allograft on bone regeneration in rats with calvarial defects, histomorphometrically and histopathologically.Material-Method: Twenty four male Wistar rats were used in this study. A 5 mm diameter critical-size defects were created in all rats using a trephine bur. The rats were divided into 4 groups; empty defect (control) (n=6), ozone application into the control defect (control+ ozone) group (n=6), defect filled with allograft (Allograft) group (n=6), ozone combined with allograft application (allograft + ozone) group (n=6). Gaseous ozone administered at 80% density for 14 days. The animals were euthanized at 8-week. Total bone area was measured histomorphometrically and osteoclast and osteoblast number were analyzed histopathologically. Results: The osteoblast numbers increased in allograft + ozone group compared to the allograft group (p<0.05). The control defects showed significantly less new bone formation than those of the allograft groups at 8 weeks (p<0.05). Total bone area was significantly higher in allograft+ozone group than those of the allograft group (p<0.05).  Conclusions: Within the limitations of this study, we suggested that allograft+ozone combination increased osteoblast number and new bone area. However, further studies are needed to investigate the mechanisms of action of ozone on bone regeneration.